(untitled) (Review of Knowledge Economy, 2019)
The study determined the effects of constructivist instructional method on low achievers’ academic performance and retention in automechanics in technical colleges. Two research questions guided the study and two hypotheses tested at 0.05 level of significance. The study was a non-randomized quasi experimental research design. The population was 121 National Technical College II (NTC II) students offering automechanics trade. Two intact classes with a sample size of 88 were purposively selected from technical colleges in the State. Automechanics Performance Test (APT) was used to collect data. Findings revealed that low achievers taught automechanics using constructivist instructional method performed better with higher post-test and retention scores than those taught with conventional method. It was concluded that constructivist instructional method could enhance students’ academic performance and retention in automechanics. Hence, teachers should be made to use the method in teaching to enable students with learning difficulties learn and retain concepts so as to improve their academic performance.